Cognitive Behavioral Therapy untuk mengurangi perilaku melukai diri pada individu dengan gangguan depresi mayor - Elma Prastika Maharani (Universitas Muhammadiyah Malang, 2022)
Depression is a mood disorder characterized by the absence of hope, prolonged sadness, excessive feelings of helplessness, inability to make decisions, inability to concentrate, loss of enthusiasm for life, feelings of tension and desire to end life or hurt oneself. The purpose of this study was to see whether self-harm behavior in depression could be reduced after giving cognitive behavioral therapy. The assessment was carried out using interviews, observation, WHO Disability Assessment Schedule (WHODAS), Depression Anxiety Stress Scales (DASS), Graphic tests (Draw a Person, BAUM, House Tree Person) and Thematic Apperception Test (TAT). The result shows that cognitive behavioral therapy is effective in reduce self-harm into positive copping mechanism behavior and can reduce negative thinking in people with depression.